Corporate Tax Avoidance in Emerging Markets: The Limited Role of ESG, Earnings Management, and Financial Leverage - Mira; Masrullah; Fitri Eka Wardani (Jurnal Riset Perpajakan: Amnesty, 2026)
This study examines the effect of earnings management and Environmental, Social, and Governance (ESG) disclosure on corporate tax avoidance, with financial leverage as a moderating variable, in LQ45 companies listed on the Indonesia Stock Exchange. Grounded in agency, stakeholder, and legitimacy theories, this research aims to provide empirical evidence on the determinants of tax avoidance behavior in emerging markets. This study employs a quantitative associative approach using secondary data from 32 LQ45 companies over the 2022–2024 period, resulting in 96 firm-year observations. Tax avoidance is proxied by the Effective Tax Rate (ETR), earnings management by discretionary accruals (DA), ESG by disclosure scores based on Global Reporting Initiative (GRI), and leverage by the Debt-to-Equity Ratio (DER). Data analysis includes multiple linear regression, classical assumption tests, hypothesis testing (t-test), coefficient of determination (R²), and Moderated Regression Analysis (MRA). The results indicate that earnings management has a negative but insignificant effect on tax avoidance, while ESG disclosure shows a positive but insignificant relationship with tax avoidance. Furthermore, leverage is not found to moderate the relationship between earnings management and tax avoidance, nor between ESG and tax avoidance. These findings suggest that earnings management, ESG performance, and leverage are not key determinants of tax avoidance among LQ45 companies. The study highlights the complexity of corporate tax behavior and implies that other factors may play a more substantial role. The results provide important insights for policymakers, investors, and regulators in improving corporate tax compliance and governance practices in emerging markets.